A MODEL FOR THE FUNCTIONAL HARMONIZATION OF MARKETPLACE RESPONSIBILITIES IN DIGITAL CONSUMER PROTECTION FOLLOWING THE 2024 AMENDMENTS TO THE ITE LAW - Oscar Prasetyo Adhi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The development of electronic commerce has positioned marketplaces as central actors in Indonesia’s digital economy. Marketplaces no longer operate merely as passive intermediaries between sellers and consumers but also function as trade facilitators, Electronic System Providers, and Personal Data Controllers. Legal issues arise because marketplace liability remains dispersed across several regulatory regimes, including the Consumer Protection Law, the Electronic Information and Transactions Law, the Personal Data Protection Law, and implementing regulations on electronic system operation and electronic commerce. This study aims to analyze the legal liability of marketplaces, identify forms of regulatory disharmony, and formulate an ideal harmonization model for digital consumer protection. This research uses normative legal methods with statutory, conceptual, and comparative approaches. The findings show that disharmony in marketplace liability occurs in four main forms: disharmony in determining the liable legal subject, the basis of liability, the scope of responsibility, and dispute resolution mechanisms. This study proposes a Functional Harmonization Model of Marketplace Liability, which allocates responsibility based on the marketplace’s functions as a trade facilitator, Electronic System Provider, and Personal Data Controller. This model is expected to strengthen legal certainty and digital consumer protection in Indonesia.